Characterization and production of IgY antibodies anti-Photobacterium damselae subsp. piscicida: Therapeutic and prophylactic use in Rachycentron canadum - Eto, Silas Fernandes [UNESP]; Fernandes, Dayanne Carla [UNESP]; Yunis-Aguinaga, Jefferson [UNESP]; Claudiano, Gustavo da Silva; Shimada, Marina Tie; Salvador, Rogério; de Moraes, Flávio Ruas [UNESP]; de Moraes, Julieta Rodini Engracia [UNESP] (Elsevier, 2019)
Pseudotuberculosis is caused by Photobacterium damselae subsp. piscicida (Phdp), an important pathogen in marine fish culture. In this study, Phdp isolated from a Rachycentron canadum farm was used to produce anti-Photobacterium damselae IgY and its protective effect were evaluated in R. canadum challenged with the homologous strain. The IgY was obtained from egg yolks of White Leghorn hens using polyethylene glycol precipitation method. Anti-Phdp IgY showed strongly specific reaction against Phdp proteins. Finally, it was performed the antibody efficacy in vivo to determinate their prophylactic and therapeutic effects during sepsis in R. canadum. For this, fish received anti-Phdp IgY 48 h and 15 days before the challenged with the homologous bacteria of Phdp. In these groups, it was observed less liver and kidney lesions comparing to control group, which was also correlated to the biochemical profile. In this study, it was also developed an immunohistochemistry test that presented highly specificity and affinity to Phdp that could be used as screening method for the diagnosis and analysis of pathogenesis of this disease. It was concluded that the IgY produced effectively inhibited the dissemination of this bacteria that could be helpful for the treatment and prophylaxis of this disease.
Keywords: Cobia fish; Immunohistochemistry; Marine fish culture; Polyclonal antibody; Teleost